Cell-cell and cell-matrix adhesion strength, local cell stiffness and forces - Mierke, Claudia (Physics of Cancer, 2018)
Cell-cell and cell-matrix adhesions are not only crucial to maintain tissue morphogenesis and provide homeostasis, they also activate signal transduction pathways, mediating many important cellular functions, including cell survival, gene expression, motility (single or collective), differentiation and adhesion. Gene mutations in adhesion receptors can evoke developmental disorders and cause different diseases such as cancer. Moreover, the cell-cell and cell-matrix adhesion strength influences the mechanical properties of cells, such as their cellular stiffness and contractile force generation. It is still under investigation which of the three main cytoskeletal structural components-actin microfilaments, keratin intermediate filaments or microtubules-contributes the most to the mechanical properties of cancer cells. Is it possible to dissect the contribution of each individual structural component to the overall mechanical properties? The answer to this question may be difficult to give, as the microfilaments can interact with intermediate filaments and microtubules, and this raises the question of whether one cytoskeletal structural component can replace another. However, quantitative methods to measure cell adhesion are therefore required to reveal how cells regulate cell-cell adhesion and cell-matrix during development and how aberrations in cell-cell and cell-matrix adhesion contribute to disease. In the following, this is described and how adhesion strength, cellular stiffness and forces can be measured with state-of-the-art biophysical methods is discussed. In particular, an overview of different in vitro techniques to study cell-cell and cell-matrix adhesion is presented such as quantitative single-cell methods based on atomic force microscopy (AFM) and a variant, AFM-based single-cell force spectroscopy (SCFS), dual micropipette aspiration (DPA), microdroplets functionalized with adhesion receptors, traction force microscopy and Forster resonance energy transfer (FRET)-based molecular tension sensors are introduced to visualize intracellular mechanical forces acting on cell-cell or cell-matrix adhesion sites.
CRIS-Team WoS Importer:2019-08-27